Physical Aging Enhanced Mesomorphic Structure in Melt-Quenched Poly(l-lactic acid) - Zhang, Tongping; Hu, Jian; Duan, Yongxin; Pi, Fuwei; Zhang, Jianming (The journal of physical chemistry. B, 2011)
The structural evolutions and kinetics of melt-quenched poly(l-lactic acid) (PLLA) during the process of isothermal physical aging below the glass transition temperature (T g) were investigated by time-resolved infrared spectroscopy. The results show that local ordered structure is developed with aging time. Such local ordered structure shows the same characteristic band at 918 cm–1 as that of the mesomorphic structure formed during the unaxially drawn process of PLLA from the glassy state. On the basis of spectroscopic evidence, we therefore proposed that the so-called local ordered structure formed by physical aging can be ascribed to a kind of mesophase of PLLA. Of particular note, a very small amount of mesophase already exists in the initial state of melt-quenched PLLA sample, whereas it is totally undetectable in the melt-quenched poly(d,l-lactide) (PDLLA) sample. By temperature-dependent IR spectroscopy, it is found that the local ordered structure formed during the physical aging process will be “partially molten” rather than “totally molten” in the temperature region corresponding to the physical aging peak of aged PLLA. Such an observation can explain the phenomenon of physical aging enhanced cold crystallization rate.